2013
DOI: 10.1002/pbc.24545
|View full text |Cite
|
Sign up to set email alerts
|

Renal function adaptation up to the fifth decade after treatment of children with unilateral renal tumor: A cross-sectional and longitudinal study

Abstract: Aging is associated with a mild-to-moderate renal function loss in many adult patients following nephrectomy during childhood for URT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 20 publications
3
46
0
Order By: Relevance
“…Recent studies indicate that NSS in unilateral WT is associated with a comparable oncological outcome as classical tumor nephrectomies [24][25][26]. At the same time there is growing evidence that late effects after tumor nephrectomy result in renal failure to a relevant degree; this seems not as much to be the case after NSS in unilateral WT [26][27][28][29][30]. The discussion process within the surgical panel of the SIOP RTSG therefore resulted in the recommendation that MIS and NSS should not interfere in terms of surgical approach: If feasible according to the guidelines of the SIOP Wilms Tumor protocol [31], NSS should be performed.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies indicate that NSS in unilateral WT is associated with a comparable oncological outcome as classical tumor nephrectomies [24][25][26]. At the same time there is growing evidence that late effects after tumor nephrectomy result in renal failure to a relevant degree; this seems not as much to be the case after NSS in unilateral WT [26][27][28][29][30]. The discussion process within the surgical panel of the SIOP RTSG therefore resulted in the recommendation that MIS and NSS should not interfere in terms of surgical approach: If feasible according to the guidelines of the SIOP Wilms Tumor protocol [31], NSS should be performed.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, children treated for WT are usually very young and the prevalence of severe renal dysfunction owing to multifactorial causes is likely to increase with longer follow-up than what is currently available. Cozzi et al [14] demonstrated a significant reduction in estimated GFR in the fifth decade of life in a group of WT survivors that underwent nephrectomy compared with healthy controls.…”
Section: Unilateral Sporadic (Nonsyndromic) Wtmentioning
confidence: 98%
“…We believe this is an open question. Although current NKF guidelines do not recognize SFK as a structural abnormality [6], several studies suggest that SFK is a risk factor for the progression of CKD [44,55,56]. Kolvek et al demonstrated that a substantial proportion of children with SFK developed renal injury defined as hypertension, severely increased albuminuria and a significantly impaired eGFR and/or use of antihypertensive or antiproteinuric medications during childhood (median age 11,0 years).…”
Section: Discussionmentioning
confidence: 99%